Portrait of a Fascist: Identity and Independence in Joseph Roth’s Das Spinnennetz (1923) - Braden M Ross (Vernacular: New Connections in Language, Literature, & Culture, 2025)
Three days before Hitler’s Beer Hall Putsch, the last chapters of Joseph Roth’s Das Spinnennetz were published in the Viennese Arbeiter-Zeitung. Detailing the decent of World War I veteran Theodor Lohse into the nascent Nazi party, Roth’s novel could not have been more prescient—and yet, it remains the least well-known of his works. Das Spinnennetz is not only a work of great fiction, but an eerie cautionary tale more prophetic than Roth could have ever imagined. In this article, I examine the metaphor of the spider’s web and how ordinary people like Lohse futility navigate their search for individual meaning within a mass movement. Focusing on aspects of gender identity and utilizing Adorno’s “Freudian Theory and the Pattern of Fascist Propaganda,” I argue that, despite efforts to find agency and meaning in the Nazi party, Lohse ends the story ironically even more dependent on the women and Jews he sought to flee, and entangled in the web of Nazi fascism.
Keywords: Joseph Roth; Das Spinnennetz; Fascism; Weimar; Identity; Independence; Mass Movement